TEACHER RELIGIOUS UNDERSTANDING AND ATTITUDE OF RELIGIOUS INCLUSIVITY IN EARLY CHILDREN AT Al-WASHLIYAH KINDERGARTEN KLAMBIR V KEBUN HAMPARAN PERAK - Mhd Habibu Rahman (Proceeding International Seminar of Islamic Studies, 2023)
The development of religious attitudes in early childhood is determined by several factors, one of which is external factors such as the religious understanding possessed by the teacher. The purpose of this study was to see the attitude of religious inclusivity of children with the teacher's religious understanding and what obstacles were found in building children's attitude of religious inclusivity in Kindergarten IT Al-Washliyah Klambir V Kebun, Hamparan Perak District, Deli Serdang Regency. The method used in this research is qualitative using Field Research. Data collection techniques were carried out by means of observation, interviews and documentation studies. Data were analyzed through the stages of data condensation, data presentation and conclusion/verification. The results of this study state that the teacher's religious understanding puts forward humanist values, is not oriented towards strengthening the doctrines and beliefs of one's own religious behavior, but rather on strengthening character and acceptance of diversity, without ignoring the religious ways of each child. The religious inclusiveness of children can be seen from the awareness of children's activities that respect the differences and diversity of the religious behavior of their friends. Obstacles found in building an attitude of religious inclusiveness in children include the level of stability in children's development which is still changing, coordination between teachers and parents that has not run optimally